ENHANCING SCHOOL PERFORMANCE THROUGH COMMUNITY PARTICIPATION IN MADAGASCAR - Léa, Soameva; Angelo, Vahinimalala Tahinarizafy; Urbain, Marolahy Jacquot (JURNAL STRATEGI PEMBELAJARAN, 2025)
This study aims to examine how community participation contributes to enhancing school performance in the Atsimo Andrefana Region of Madagascar. Schools in this region face persistent challenges, including limited resources, low student motivation, high absenteeism, and socio-economic constraints, which affect learning outcomes and overall institutional effectiveness. A qualitative case study approach was adopted, involving 38 key participants, including school principals, vice principals, guidance counselors, teachers, parent association leaders, community leaders, local education office representatives, and student representatives. Data were collected through semi-structured interviews, non-participant observations, and document analysis, and were analyzed thematically to capture patterns and insights across multiple stakeholder perspectives. The findings indicate that active community participation enhances student motivation, attendance, and engagement while contributing to a more supportive and organized school environment. Integration of local knowledge, such as cultural practices and practical skills, strengthened the relevance of learning and promoted collaborative problem-solving between schools and communities. Challenges to sustaining school–community partnerships included socio-economic limitations, geographic isolation, communication barriers, and gaps in teacher training; however, informal contributions and culturally grounded initiatives demonstrated measurable positive effects on student outcomes. The study underscores the need for structured and flexible strategies to maintain engagement, capacity-building for educators and community stakeholders, and institutional mechanisms that support long-term collaboration. Future research could explore the longitudinal impacts of collaborative learning ecosystems and conduct comparative studies across different regions to identify effective strategies for community-supported education in Madagascar